Socio economic factors of child basic immunization: Case of West Java Province - Patrisia Helena Saraswati; Ascobat Gani (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Indonesia has committed to eradicating infectious diseases by launching an Expanded Program on Immunization (EPI) in 1977 with a focus on 6 diseases: tuberculosis, diphtheria, tetanus, pertussis, measles, and polio. According to the Basic Health Survey (RISKESDAS) 2018, the rate of basic immunization coverage for children in Indonesia was still below 60% and coverage between provinces varies. West Java was among the province with low child basic immunization coverage. The current study is designed to examine the socio-economic factors that influence child basic immunization using logistic regression. Socioeconomic data were extracted from the National Socioeconomic Survey (Susenas) 2017 and Village Potential (Podes) Survey 2018. The study finds that income, maternal education, location of residence, insurance ownership, availability of health facilities and health workers increase the likelihood of children getting immunized.